Dynamic interplay of soil parameters and CO2 sequestration in Solanku-runi Freshwater Pond Wetland, Tamil Nadu, India - Palsamy, Packiaraj; Gayathrippriya, S.; Chinnakaruppan, M.; Premkumar, M.; Krishnan, S. Gopala; Muthuvel, U; Suresh, K. (Journal of Agriculture and Applied Biology, 2024)
This study investigates the dynamic interplay between soil temperature, pH levels, and CO2 sequestration across ten sample sites over a four-month periods from January to April 2018 in Solankuruni freshwater pond wetland in Madurai District, Tamil Nadu, India. The soil temperature fluctuations, ranging from 31°C to 44°C, reveal distinct site-specific patterns, with sample site six consistently exhibiting the highest temperatures. Soil temperature exhibited notable variations, influenced by factors such as soil composition, and microclimate variations. Regarding pH level, the range between 6.23 to 8.1 display variability influenced by factors like soil composition and anthropogenic influences, study site five consistently leading in pH levels. Soil CO2 sequestration varying from 1517.857 g/m² to 3357.143 g/m², highlight the influence of soil microbial activity, vegetation cover, and soil moisture content, ninth site consistently showing the highest sequestration rates. The findings reveal substantial variations in factors such as soil composition, vegetation type, microclimate, and anthropogenic activities, prominence the intricate nature of soil dynamics. These results stress the importance of understanding the interconnections among soil properties to create effective climate change mitigation strategies. Moreover, the research provides valuable understanding of the intricate connections between soil properties, emphasizing the necessity for region-specific studies to inform comprehensive environmental policies. Understanding these dynamic soil processes is crucial for advancing sustainable land management practices and boosting soil carbon sequestration in wetland ecosystems.